Attention to Social Media Ads: The Role of Consumer Recommendations and Smartphones. Issue 3 (2nd September 2021) - Maslowska, Ewa; Ohme, Jakob; Segijn, Claire M.
Abstract: Despite the increasing presence of advertising on social media, research looking into the relative effects of social media ads is limited and highly dependent on either self-report or basic engagement metrics (e.g., likes). Our understanding of social media advertising is further complicated by (1) constantly changing advertising strategies, such as inclusion of consumer recommendations, and (2) the role of the device used to access social media. In an eye-tracking study ( n  = 121), we investigate whether consumers dedicate different levels of attention to an ad in a social media newsfeed depending on consumer recommendation (with versus without) and type of device (smartphone versus desktop personal computer [PC]). To increase ecological validity, this study uses a scrollable social media feed in combination with a mobile eye tracker. We find that consumers pay similar attention to the social media ad across recommendation conditions and devices. The results of this study suggest that the effects of advertisements may be smaller than previously assumed and call for more research using more realistic and dynamic exposure situations.